The canning of three species of Philippine shrimps - Urrutia, Leonor del Rosario; Guzman, Matilde P. (1965.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Canned shrimp; Shrimps -- Philippines